Assessing the ease of conversation in multi-group conversation spaces: Effect of background music volume on acoustic comfort in a café. Issue 2 (June 2020) - Maruyama, Naoya; Hiraguri, Yasuhiro; Kawai, Keiji; Ueda, Mari
A "multi-group conversation space" refers to a space, such as restaurant or café, where more than one group of people share a space and make conversation within their respective group. From a field experiment in an actual café, we investigated the acoustic comfort in a multi-group conversation space considering speech intelligibility and speech privacy as major factors. In the experiment, noise measurements and a questionnaire survey taken by customers were conducted for 4 days. We were able to change the volume of the background music during operating hours, setting the level on each of the 4 days to low, mid, high, and none . Indoor noise levels were measured at six representative points with six sound level meters hung from the ceiling. The questionnaire consisted of eight items for subjective evaluation, including ease of conversation, comfort, and room atmosphere. After having their meal or drinks, the customers were asked to fill in the questionnaire at their table. The occupancy of neighboring tables and the number of customers in the café were also recorded. Results show that (1) overall, the respondents evaluated the café space positively; (2) high background music volume levels together with occupied neighboring tables tended to elicit negative evaluations; and (3) customer clustering analysis identified certain influences of distance from loudspeakers, neighboring table occupancy, and personal characteristics.